The journal of James Edmond Pease, a Civil War Union soldier - Murphy, Jim, 1947-2022. (New York : Scholastic Inc., 1998)
James Edmond, a sixteen-year-old orphan, keeps a journal of his experiences and those of "G" Company which he joined as a volunteer in the Union Army during the Civil War.
Keywords: United States -- History -- Civil War, 1861-1865 -- Juvenile fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; Diaries -- Fiction; Orphans -- Fiction; Diaries -- Juvenile fiction; Orphans -- Juvenile fiction